Dual Topology of the Melanocortin-2 Receptor Accessory Protein Is Stable - Maben, Zachary J.; Malik, Sundeep; Jiang, Liyi H.; Hinkle, Patricia M. (Frontiers in Endocrinology, 2016)
MRAP (melanocortin 2 receptor accessory protein) facilitates trafficking of melanocortin 2 (MC2) receptors and is essential for ACTH binding and signaling. MRAP is a single transmembrane domain protein that forms antiparallel homodimers. These studies ask when MRAP first acquires this dual topology, whether MRAP architecture is static or stable, and whether the accessory protein undergoes rapid turnover. To answer these questions we developed a novel approach that capitalizes on the specificity of bacterial biotin ligase, which adds biotin to lysine in a short acceptor peptide sequence; the distinct mobility of MRAP protomers of opposite orientations based on their N-linked glycosylation; and the ease of identifying biotin-labeled proteins. We inserted biotin ligase acceptor peptides at the N- or C-terminal ends of MRAP and expressed the modified proteins in mammalian cells together with either cytoplasmic or endoplasmic reticulum-targeted biotin ligase. MRAP assumed dual topology early in biosynthesis in both CHO and OS3 adrenal cells. Once established, MRAP orientation was stable. Despite its conformational stability, MRAP displayed a half life of under 2 hr in CHO cells. The amount of MRAP was increased by the proteasome inhibitor MG132 and MRAP underwent ubiquitylation on lysine and other amino acids. Nonetheless, when protein synthesis was blocked with cycloheximide, MRAP was rapidly degraded even when MG132 was included and all lysines were replaced by arginines, implicating non-proteasomal degradation pathways. The results show that although MRAP does not change orientations during trafficking its synthesis and degradation are dynamically regulated.